The Nonbank-Bank Nexus and the Shadow Banking System - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2011)
The present way of thinking about financial intermediation does not fully incorporate the rise of asset managers as a major source of funding for banks through the shadow banking system. Asset managers are dominant sources of demand for non-M2 types of money and serve as source collateral ?mines' for the shadow banking system. Banks receive funding through the re-use of pledged collateral ?mined' from asset managers. Accounting for this, the size of the shadow banking system in the U.S. may be up to USD 25 trillion at year-end 2007 and USD 18 trillion at year-end 2010, higher than earlier estimates. In terms of policy, regulators will need to consider the re-use of pledged collateral when defining bank leverage ratios. Also, given asset managers' demand for non-M2 types of money, monitoring the shadow banking system will warrant closer attention well beyond the regulatory perimeter.